2015
DOI: 10.1186/s13256-015-0542-7
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 infection presenting with severe erythroid aplastic crisis during pregnancy in a woman with autoimmune hemolytic anemia and alpha-thalassemia trait: a case report

Abstract: IntroductionParvovirus B19 virus commonly causes subclinical infection, but it can prove fatal to the fetus during pregnancy and cause severe anemia in an adult with hemolytic diseases. We present the case of a woman with autoimmune hemolytic anemia who was diagnosed with parvovirus B19-induced transient aplastic crisis during her second trimester of pregnancy and faced the high risk of both fetal and maternal complications related to this specific viral infection. To the best of our knowledge, the experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…19-infected erythroblast cells with intranuclear inclusions have been observed in placenta and fetal tissue by many authors with histology and electron microscopy methods [1,3,5]. In our research the histopathological assessment of placenta in case of parvovirus infection is characterized by pronounced placentitis with edema due to the cytolytic action of viruses in the core of endothelial cells of the blood capillaries, as well as in the cytoplasm, myelin-like structures, which contributes to the enhancement of lipid peroxide oxidation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…19-infected erythroblast cells with intranuclear inclusions have been observed in placenta and fetal tissue by many authors with histology and electron microscopy methods [1,3,5]. In our research the histopathological assessment of placenta in case of parvovirus infection is characterized by pronounced placentitis with edema due to the cytolytic action of viruses in the core of endothelial cells of the blood capillaries, as well as in the cytoplasm, myelin-like structures, which contributes to the enhancement of lipid peroxide oxidation.…”
Section: Discussionmentioning
confidence: 55%
“…Maternal alpha-fetoprotein is correlated with both Doppler blood flow velocity parameters in the middle cerebral artery and fetal hemoglobin. Elevations of this marker may appear earlier than Doppler abnormalities in cases of fetal anemia associated with hydrops [3].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A case of maternal severe transient aplastic crisis, on the background of shortened lifespan of erythrocytes, was recently reported due to B19 infection during pregnancy [ 21 ]. In addition, Rajput et al reported a case of severe aplastic anemia in a previously healthy adult female because of acute parvovirus B19 infection [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Гістологія ембріонів, інфікованих парвовірусом, показала значне зменшення еритропоетичних островців у паренхімі печінки. Вчені зробили висновок, що вплив ПВ19 може бути небезпечним для гемопоетичної системи плода, оскільки кількість незрілих попередників еритроцитів та інтенсивність гемопоезу плода в 3-5 разів перевищують дорослу форму гемопоезу у плода з тяжкою фетальною анемією (ФА) [14,21,31]. Цитоморфологічні дослідження плаценти та тканини серця інфікованих загиблих плодів доводять, що ПВ19 має цитолітичний вплив на ендотеліальні клітини плаценти, викликає апоптоз клітин трофобласту, вражає печінку плода, а також є чинником фетального міокардиту [9,15].Внаслідок ураження ланок кровоутворення у плода розвивається стійка лейкопенія за рахунок різкого зменшення нейтрофілів та тромбоцитопенія [16].…”
Section: резюмеunclassified